STRATEGI MEWUJUDKAN PROFIL PELAJAR PANCASILA PADA ANAK TK MELALUI NILAI - NILAI KEARIFAN LOKAL - Lina Kamalia Zahra; Sumarno; Idadwijayanti (STKIP Subang, 2024)
The aim of this research is to provide an overview of the importance of strategies to realize the Pancasila student profile in kindergarten children through local wisdom values. The method used is a survey with a questionnaire instrument and numerical data which includes the frequency of learning local wisdom. The research population was 50 children, but only 45 children attended, and only 40 children responded to questions. Questionnaires were also given to 50 parents but only 38 parents filled out the questionnaire and 4 teachers at the Aisyiyah Bustanul Athfal Jatimulyo Kindergarten. From the results of data analysis, 25 children did not like traditional food and drinks. 15 children said they liked it. Of the 38 parents who often served food at home, 15 people chose tempeh, 10 people answered tofu and 13 people served sausages. And regarding traditional games, out of 40 children, only 4 children know traditional games. All 4 teachers answered that they had never prepared learning plans related to local wisdom. Based on the results of data analysis, it was concluded that children did not know local wisdom at the Aisyiyah Bustanul Athfal Jatimulyo Kindergarten because one of the reasons the teacher had not included it in the activity planning.